Pediatric posterior trans-olecranon fracture-dislocation of the elbow: a case report and review of literature - Xiang, Ren; Qingsong, Tang; Kang, Zhao; Jie, Hu (Frontiers in Surgery, 2025)
ObjectiveDislocations of the elbow are not common in skeletally immature patients. Herein, we present a case report on a rare pediatric posterior trans-olecranon fracture dislocation of the elbow, a type of dislocation that has never been reported in children. We aim to discuss the injury mechanism and introduce our treatment approach for this specific condition.PatientA ten-year-old girl presented with pain, swelling and deformity of the left elbow following a fall from a rocking chair.Diagnoses and interventionsThe complete injury history and detailed physical examination were recorded. Radiographs revealed fractures affecting the coronoid process of the ulna, olecranon of the ulna, radial neck, along with dislocation of radiocapitellar joint, and posterior medial displacement of proximal radial-ulnar joint. Based on these findings, the diagnosis of posterior trans-olecranon fracture dislocation of the elbow was made. To restore stability of the elbow, open reduction and internal fixation were performed. This involved securing the coronoid process of the ulna with the suture lasso technique and stabilizing the olecranon of the ulna with two 2.0 mm Kirschner wires inserted into the medullary cavity. The wires were subsequently removed at 2 months postoperatively.OutcomesThree months after the initial surgery, which is one month after the removal of internal fixation, the affected elbow joint achieved a range of motion of 140° flexion and 0° extension, with no limitation in forearm rotation activities. The elbow joint was stable and painless during movement. At the one-year follow-up, no difference was observed in the function of the bilateral elbow joints, and imaging examinations showed normal anatomical relationships of the elbow joints.ConclusionThis specific type of injury, termed as posterior trans-olecranon fracture-dislocation of the elbow, is rare and has few reports in the pediatric population. We, hereby, report the case to emphasize the importance of promptly restoring the stability of the elbow and initiating early actively range-of-motion exercises to ensure a favorable outcome.